Malaysian Companies Act 2016: Impact of the Rule of Law on Fiduciary Duties of Directors. - Balasingam, Usharani (International Journal of Engineering and Technology, 2018)
The business world is run by the use of legal vehicles including a private limited or public company driven by directors. The duties and responsibilities of directors and the board of directors who run the company to the shareholders in a solvent company is paramount to ensure business is done in the best interest of the company. It is necessary for businesses to be confident of the mechanism that exists in any country for the directors who are in positions of power to be held accountable so as not to abuse their trust.Â This has been regulated by statute and by rule of law (common law and equitable principles) to ensure accountability, fidelity and loyalty of the directors. However the revised Malaysian Companies Act 2016 has consequence and impact in this regard to the existing law by deliberating omitting existing reference to rule of law as a basis of liability. Hence this paper will in its method examine the provision of law both statute and common law of the old and current law to consider the impact on businesses and directors in Malaysia given the new Malaysian Companies Act 2016. There will be discussion on the effect of the provisions by reference to statute and case law. Findings of the changes and possible implications will be made in the paper.Â Â